Peran Gender sebagai Moderator dalam Hubungan Penilaian Kinerja Manajerial dan Perilaku Disfungsional (Lembaga Pengembangan Kinerja Dosen, 2025)
Managerial performance appraisal plays a crucial role in assessing managers' effectiveness in achieving organizational goals. Through this assessment, organizations can measure managers' contributions to target achievement and provide valuable feedback for competency development. However, in practice, performance appraisals are often not entirely objective due to the influence of external factors, one of which is gender. Gender bias in performance evaluations can lead to unfairness, which can lead to dysfunctional behavior, behavior that conflicts with organizational interests. This study aims to examine the effect of managerial performance appraisals on dysfunctional behavior by incorporating gender as a moderating variable. The study was conducted at Putra Baru Swalayan, Central Lampung, using a quantitative approach. Data were obtained through the distribution of closed-ended questionnaires to 85 respondents selected using a purposive sampling technique. Data analysis was performed using moderated regression using SPSS version 20 software. The results showed that managerial performance appraisals significantly influenced dysfunctional behavior. The lower the performance appraisal received, the higher the manager's tendency to engage in dysfunctional behavior, such as decreased motivation, the emergence of conflict, or behavior detrimental to the organization. Furthermore, gender was shown to moderate this relationship. The findings indicate a gender bias in evaluations, with female managers tending to receive lower ratings than male managers. This unfairness has the potential to increase the risk of dysfunctional behavior among those who feel disadvantaged. These findings have important implications for organizations. Performance evaluation systems need to be designed to be fairer, more transparent, and more gender-sensitive to minimize bias. This way, organizations can reduce the potential for dysfunctional behavior while creating a healthier, more inclusive, and more productive work environment.